Body and peripersonal space representations in chronic stroke patients with upper limb motor deficits. Issue 4 (5th August 2022) - Bassolino, Michela; Franza, Matteo; Guanziroli, Eleonora; Sorrentino, Giuliana; Canzoneri, Elisa; Colombo, Maria; Crema, Andrea; Bertoni, Tommaso; Mastria, Giulio; Vissani, Matteo; Sokolov, Arseny A; Micera, Silvestro; et al.
Abstract: The continuous stream of multisensory information between the brain and the body during body–environment interactions is crucial to maintain the updated representation of the perceived dimensions of body parts (metric body representation) and the space around the body (the peripersonal space). Such flow of multisensory signals is often limited by upper limb sensorimotor deficits after stroke. This would suggest the presence of systematic distortions of metric body representation and peripersonal space in chronic patients with persistent sensorimotor deficits. We assessed metric body representation and peripersonal space representation in 60 chronic stroke patients with unilateral upper limb motor deficits, in comparison with age-matched healthy controls. We also administered a questionnaire capturing explicit feelings towards the affected limb. These novel measures were analysed with respect to patients' clinical profiles and brain lesions to investigate the neural and functional origin of putative deficits. Stroke patients showed distortions in metric body representation of the affected limb, characterized by an underestimation of the arm length and an alteration of the arm global shape. A descriptive lesion analysis (subtraction analysis) suggests that these distortions may be more frequently associated with lesions involving the superior corona radiata and the superior frontal gyrus. Peripersonal space representation was also altered, with reduced multisensory facilitation for stimuli presented around the affected limb. These deficits were more common in patients reporting pain during motion. Explorative lesion analyses (subtraction analysis, disconnection maps) suggest that the peripersonal space distortions would be more frequently associated with lesions involving the parietal operculum and white matter frontoparietal connections. Moreover, patients reported altered feelings towards the affected limb, which were associated with right brain damage, proprioceptive deficits and a lower cognitive profile. These results reveal implicit and explicit distortions involving metric body representation, peripersonal space representation and the perception of the affected limb in chronic stroke patients. These findings might have important clinical implications for the longitudinal monitoring and the treatments of often-neglected deficits in body perception and representation. Abstract : Bassolino et al . studied body perception in post-stroke chronic patients with upper limb sensorimotor deficits. Results reveal distortions in the perceived dimensions, representation of peripersonal space and explicit feelings towards the affected limb. This motivates quantitative assessments of body perception even in later phases after stroke. Graphical Abstract: Graphical Abstract